Manejo Agronómico del cultivo de Pomarrosa (Syzygium malaccense) en Ecuador - López Tuarez, Carlos Eduardo (2022)
This document refers to the agronomic management of Pomarrosa (Syzygium malaccense) cultivation. Agronomic management, through the set of activities or tasks, aims to provide the crop with the best development and growth conditions in order to approach the crop's yield potential and obtain the best profitability results. The pomarrosa is adaptable to any type of soil, whether poor or medium poor in nutrients. The conclusions determine that there are no continuous investigations, in terms of seeds, soils, irrigation systems, agronomic behavior, regarding the production of pomarrosa. In Ecuador there are few areas of pomarrosa production, due to the fact that it is not a traditional crop and also due to lack of knowledge regarding agronomic management and the multiple benefits that can be obtained from the crop. Among the main uses given to the pomarrosa we have that its leaves have medicinal properties to treat infections in the mouth and throat, its fruit serves as food and also to make juices and syrup, the tree can be ornamental due to the combination of leaves and flowers, its wood can be used in the manufacture of furniture and stakes. It is recommended to encourage producers to cultivate pomarrosa for the various benefits obtained from the crop and also as an alternative to improve their economic income.